2020
DOI: 10.1111/jvs.12970
|View full text |Cite
|
Sign up to set email alerts
|

Disturbance effects on productivity–plant diversity relationships from a 22‐year‐old successional field

Abstract: Aims: The productivity-plant diversity relationship is a central subject in ecology under debate for decades. Anthropogenic disturbances have been demonstrated to affect productivity and plant diversity. However, the impact of disturbances on the productivity-diversity relationship is poorly understood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 87 publications
(140 reference statements)
0
3
0
Order By: Relevance
“…This hypothesis has been mainly tested by assessing the relationship between native and non-native species richness. This relationship is strongly context dependent and varies with the spatial scale of the study, in observational versus experimental studies (9,49,85,155,194,268), and with environmental conditions, such as environmental stress (280), productivity (47), and disturbance (156). In general, the sign of this relationship changes from negative to positive with increasing spatial scale (77,247,265), constituting the so-called invasion paradox.…”
Section: Importance Of Competition and Facilitationmentioning
confidence: 99%
See 1 more Smart Citation
“…This hypothesis has been mainly tested by assessing the relationship between native and non-native species richness. This relationship is strongly context dependent and varies with the spatial scale of the study, in observational versus experimental studies (9,49,85,155,194,268), and with environmental conditions, such as environmental stress (280), productivity (47), and disturbance (156). In general, the sign of this relationship changes from negative to positive with increasing spatial scale (77,247,265), constituting the so-called invasion paradox.…”
Section: Importance Of Competition and Facilitationmentioning
confidence: 99%
“…To unify theories on invasiveness and invasibility, MacDougall and colleagues (167) suggested that this issue should be examined with regard to niche and fitness differences. The presence of empty niches or trait space (180) unoccupied by native species, resulting from differences in resource use (156), would facilitate the establishment of non-native species through competition avoidance. By contrast, in the absence of niche differences, fitness differences (i.e., differences in the competitive ability, fecundity, or susceptibility to predators and pathogens) would result in competitive exclusion by species with the highest average fitness.…”
Section: Importance Of Competition and Facilitationmentioning
confidence: 99%
“…Mechanistically, the unimodal relationship of HBMs along productivity gradients is attributed to high stress resulting in low productivity and few species, followed by increased susceptibility to facilitation as improved environmental conditions allow for more species and high productivity until an optimum is reached; subsequently, the stress decreases with decreased diversity as interspecific competition increases with high productivity of dominant species (Michalet et al 2006). However, while the HBM is globally robust (Fraser et al 2015), support is context dependent (Catford et al 2022) due to anthropogenic limitations on the species pool (Adler et al 2011), aridity (Rey et al 2016), sampling bias (Oksanen 1996), nutrient limitation (Palpurina et al 2019), and other abiotic contingencies, such as disturbance or successional progression (Guo 2003;Li et al 2021;Ónodi et al 2021). One context of the HBM that has not been explored is whether diversity-productivity relationships are influenced by locally adapted ecotypes of the dominant species that contribute most to productivity.…”
Section: Introductionmentioning
confidence: 99%